The Influence of Regional Own-Source Revenue, General Allocation Funds, Special Allocation Funds, and Capital Expenditure on Regional Financial Independence Through Economic Growth in North Sulawesi Province - Tuwaidan, George Kevin; Masinambow, Vecky A.J.; Kawung, George M.V. (CV. Publikasi Indonesia, 2024)
In the context of fiscal decentralization in Indonesia, regional financial independence represents a significant challenge, given the considerable dependence on central fund transfers, including the General Allocation Fund (DAU) and the Special Allocation Fund (DAK). This issue is further compounded by suboptimal management of local own-source revenues (PAD) and ineffective capital expenditure allocations, which have a detrimental impact on infrastructure development and economic growth. Fiscal imbalances between regions also contribute to the widening of economic disparities, impeding efforts to achieve sustainable financial independence. This study aims to analyze the influence of Regional Original Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), and Capital Expenditure on the level of regional financial independence through economic growth in North Sulawesi Province. Using secondary data from the 2011-2023 period, the path analysis method was applied to evaluate the direct and indirect relationships between variables. The results of the study show that PAD has a significant positive effect on economic growth and regional financial independence. DAU and DAK, although contributing to fiscal needs, show varying influences on economic growth and financial independence. These findings emphasize the importance of optimizing PAD and capital expenditure allocation to support economic development and reduce dependence on central fund transfers.